Pertanggungjawaban Direksi yang Bertindak Melebihi Keputusan Rapat Umum Pemegang Saham - Ikfina Himmati Faricha; Gracia Tribuana Wibowo (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The director is an organ that plays an important role in determining the progress or resignation of a company legally. It is important that the management's role is reflected in the duties and responsibilities attached as announced in Law No. 40 of 2007. The Director shall be fully responsible for the management of the appeal in the interests of the appeal in accordance with the purpose and purpose of the appeal and shall represent the appeal either within or outside the court in accordance with the basic budget. However, in its implementation there are those that do not comply with the rules already laid down and what has been agreed on in the basic budget. It can therefore be concluded that the Directorate may act in excess of what is in its power and not in accordance with the outcome of the General Meeting of Volunteers. As for directors who exceed the limits of their duties and functions and who are not in accordance with the General Meeting of Securities Holders, the answer may also be sought.